Black and slave? "Mestizo" Augustine on Ham - Oort, Johannes van (HTS teologiese studies, 2023)
After discussing the so-called Ham myth in South Africa, my focus is on the African church father Augustine (354–430). All texts from his immense oeuvre in which he mentions biblical Ham are reviewed in chronological order. In Against Faustus, the story of Noah and his sons is mainly explained as being Christological: Ham figures as a type of the unbelieving Jews who consented to the murder of Christ, but he is also a type of the Jews because he is ‘the slave of his brothers’ carrying the books by which the Christians may be instructed. Later Augustine corrects his confusion of Ham with the slave Canaan. The story of Ham (and Canaan) is most extensively discussed in the City of God. Neither here nor in the Expositions on the Psalms, Ham is described as being black or a slave. The same goes for a number of his other writings. In Augustine’s late works Against Julian and Unfinished Work against Julian, he thoroughly goes into the question of why (although Ham sinned) ‘vengeance was brought upon Canaan’. Augustine perceives God’s prophecy: from Canaan stems the cursed seed [semen maledictum] of the Canaanites. Nowhere, however, he claims that Ham or his descendants would have been cursed to be black or that all of his offspring were condemned to slavery.Contribution: This article demonstrates that the Ham myth does not occur in Augustine. It argues that the ‘mestizo’ African Augustine might have been extra sensitive to questions of race and colour.